2016
DOI: 10.1016/j.neurobiolaging.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in progranulin gene associated with frontotemporal lobar degeneration: study of pathogenetic features

Abstract: GRN, the gene coding for the progranulin (PGRN), was recognized as a gene linked to frontotemporal lobar degeneration (FTLD). The first mutations identified were null mutations giving rise to haploinsufficiency. Missense mutations were subsequently detected but only a small subset has been functionally investigated. We identified missense mutations (C105Y, A199V and R298H) in FTLD cases with family history and/or with low plasma PGRN levels. The aim of this study was to determine their pathogenicity. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
(85 reference statements)
3
10
0
Order By: Relevance
“…A functional study showed that the p.R298H variant produced a moderate effect on PGRN secretion. [11] Our data support the pathogenic role of GRN p.R298H variant in FTD, since it was first found in two Italian sisters with FTD and family history of behavioral disturbances and dementia.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A functional study showed that the p.R298H variant produced a moderate effect on PGRN secretion. [11] Our data support the pathogenic role of GRN p.R298H variant in FTD, since it was first found in two Italian sisters with FTD and family history of behavioral disturbances and dementia.…”
Section: Discussionsupporting
confidence: 87%
“…The mutation was detected in only one patient with pathologically confirmed FLTD with ubiquitin-positive inclusions and unknown family history. [10] The same variant was also reported by Karch et al [11] in one FTLD patient presenting at 71 years with a typical corticobasal syndrome and a family history of dementia. A functional study showed that the p.R298H variant produced a moderate effect on PGRN secretion.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Most pathogenic alterations in GRN gene are either frameshift or nonsense mutations causing premature termination of the coding sequence and degradation of the mutant RNA by nonsense-mediated decay [ 18 ]. However, point mutations disrupting the structure of the protein are also strongly suspected to be pathogenic [ 19 ]. Loss-of-function mutations in the GRN gene cause haploid insufficiency of progranulin, whose plasma levels decrease as a consequence [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Variants in GRN were detected in three subjects (3%). Two carried the same mutation (c.G314A, p.C105Y), previously shown to affect both the secretion of PGRN in cultured cells and the elastase cleavage of PGRN into GRN 24 . One patient (RSA_bvFTD_50) referred as apparently sporadic, carried two different variants in GRN .…”
Section: Resultsmentioning
confidence: 99%